Consideration of Judges in PPh Correction Disputes Article 23: Review of PK Decision Number 5360/B/PK/CHD/2024 - Sitompul, Ariman (International Asia Of Law and Money Laundering, 2025)
This article analyzes in depth the legal considerations of the Supreme Court in the judicial review decision (PK) number 5360/B/PK/Chjk/2024 relating to the dispute over the correction of Income Tax (PPh) Article 23 on the payment of the coal selling commission by PT Arzara Baraindo Energitama to PT Maceral Energitama. The dispute stems from differences in interpretation between taxpayers and tax authorities regarding the juridical character of the payment, whether it is a remuneration for services included in the object of withholding income tax Article 23, disguised dividends, or not both. The Directorate General of taxes determined the correction on the basis that the payment was not supported by evidence of the provision of real services and did not qualify as a deductible expense under the tax provisions.The Tax Court, through the previous ruling, confirmed that the coal selling commission did not meet the characteristics of Service Remuneration as stipulated in Article 23 of the Income Tax Law and was also not a dividend as referred to in Article 4 paragraph (1) letter g of the Income Tax Law. However, the court retained the correction of the DGT because the payment did not meet the criteria for deductible expenses under Article 6 paragraph (1) of the Income Tax Law. The Supreme Court in the PK level affirms Judex Facti consideration by stating that the subject matter of the dispute is closely related to the assessment of facts, so it is beyond the scope of the PK examination which can only be submitted on the basis of real errors, errors of judges, or the discovery of new evidence (novum).Through the approach of normative legal research and analysis to the construction of judges ' considerations, this article finds that the Supreme Court affirms important legal positions: (1) PK cannot be used to re-examine the facts that have been examined in the trial of the previous level; (2) the economic substance of a transaction becomes a valid basis for making tax corrections; and (3) evidence related to the character of the transaction and the existence of services is within the taxpayer's burden. This ruling has significant practical implications for the consistency of the application of tax law, the legal certainty of tax administration, as well as the limitation of judicial authority in tax disputes.